Positive electrode material and preparation method thereof, positive electrode plate and secondary battery

By introducing tungsten, boron and cerium elements into high-nickel cobalt-free cathode materials for coordinated doping, the problems of instability of the material structure and serious interface side reactions are solved, and its circulation and rate performance is significantly improved.

CN119786592APending Publication Date: 2025-04-08WUYI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411913350.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The high-nickel cobalt-free cathode material has unstable structure and severe interface side reactions during the circulation process, resulting in poor circulation and rate performance.

Method used

By introducing tungsten, boron and cerium elements for coordinated doping, the internal structure, surface stability and particle morphology of the material are optimized to form an α-NaFeO2-type layered structure.

Benefits of technology

The circulation capacity retention and rate performance of high-nickel cobalt-free cathode materials are significantly improved, and the thermal stability and comprehensive electrochemical performance of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786592A_ABST
    Figure CN119786592A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode material and a preparation method thereof, a positive electrode plate and a secondary battery. The chemical formula of the positive electrode material is LiNi (1-x-y-z) WxCeyBzO2, wherein 0 < x < = 0.01; 0 < y < = 0.01; 0 < z < = 0.01. The tungsten element, the boron element and the cerium element are introduced to synergistically dope the high-nickel cobalt-free positive electrode material, so that the cycle life, the rate capability and the capacity retention ratio of the high-nickel cobalt-free positive electrode material are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode plate and a secondary battery. Background Art

[0002] As the global demand for clean energy increases, lithium-ion batteries have been widely used in electric vehicles, energy storage systems, consumer electronics and other fields due to their high energy density and long cycle life. Traditional lithium-ion battery positive electrode materials usually use nickel-cobalt-manganese (NCM) or nickel-cobalt-aluminum (NCA) systems, which improve the stability of the battery by adding cobalt (Co). However, cobalt resources are scarce and expensive, and the mining process will cause environmental pollution and social problems. In order to reduce the cost of lithium-ion batteries and reduce the impact on the environment, the development of cobalt-free positive electrode materials has become an important direction for battery research and industrial development.

[0003] In the cobalt-free system, high-nickel cathode materials (Ni content ≥ 90%) have gradually attracted attention due to their high energy density and cost potential. However, the practical application of high-nickel materials still faces many technical challenges, such as:

[0004] 1. Structural instability: During the cycle, high nickel materials are prone to lattice distortion and irreversible phase change, resulting in poor cycle performance; 2. Serious interface side reactions: The reaction with the electrolyte leads to product accumulation, further hindering lithium ion transmission, resulting in poor rate performance.

[0005] Therefore, it is necessary to develop a high-nickel, cobalt-free cathode material with better cycle performance and rate performance. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention provides a positive electrode material with high structural stability and low interface side reactions, so that the cycle performance and rate performance of the secondary battery are higher.

[0007] The second aspect of the present invention also provides a method for preparing a positive electrode material.

[0008] The third aspect of the present invention also provides a positive electrode plate.

[0009] A fourth aspect of the present invention also provides a secondary battery.

[0010] According to the first aspect of the present invention, a positive electrode material is provided, wherein the chemical formula of the positive electrode material is LiNi (1-x-y-z) W x Ce y B z O2; wherein, 0<x≤0.01; 0<y≤0.01; 0<z≤0.01.

[0011] The positive electrode material according to the embodiment of the present invention has at least the following beneficial effects:

[0012] The present invention introduces tungsten, boron and cerium elements to synergistically dope the high-nickel cobalt-free positive electrode material, thereby greatly improving the cycle capacity retention rate and rate performance of the high-nickel cobalt-free positive electrode material.

[0013] This is because the three doping elements work together at different levels, achieving all-round synergy from internal structure to surface stability to particle morphology optimization: tungsten (W) provides a stable foundation for the crystal structure, avoiding the structural collapse of the material in long cycles; cerium (Ce) modifies the surface reaction environment, reduces interface side reactions and enhances interface stability; boron (B) particle refinement supplements the optimization of the transmission level, improves mechanical stability, reduces internal resistance and improves rate performance. Through the synergistic optimization of these three elements, the material's cycle performance, rate performance and thermal stability have been significantly improved, showing better comprehensive electrochemical performance.

[0014] According to a preferred embodiment of the present invention, an α-NaFeO2 type layered structure is formed in the positive electrode material.

[0015] According to a preferred embodiment of the present invention, the average particle size of the secondary particles of the positive electrode material is 8 μm to 16 μm.

[0016] In the present invention, the average particle size of the secondary particles of the positive electrode material is a well-known meaning in the art, also known as the median particle size, which indicates the particle size corresponding to 50% of the volume distribution of the secondary particles. The average particle size can be measured by instruments and methods well-known in the art, for example, it can be conveniently measured by a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK.

[0017] According to a second aspect of the present invention, there is provided a method for preparing a positive electrode material, comprising the following steps:

[0018] S1, mixing a nickel source, a tungsten source, a cerium source, a boron source and a lithium source and ball milling them to obtain a precursor;

[0019] S2, sintering the precursor to obtain an intermediate;

[0020] S3. Sintering the intermediate II and grinding it to obtain a positive electrode material.

[0021] The method for preparing the positive electrode material according to the embodiment of the present invention has at least the following beneficial effects:

[0022] The present invention firstly ball-mills each raw material; and then respectively performs sintering I and sintering II to obtain a positive electrode material. The method can provide uniformity of W element doping and crystal structure stability; improve the first discharge specific capacity of the material; enhance the stability of cerium element surface doping and optimize the effect of boron element particle refinement; and improve the interface stability and anti-side reaction ability of the material.

[0023] According to a preferred embodiment of the present invention, the sintering temperature of the sintering I is 680-720°C.

[0024] According to a preferred embodiment of the present invention, the sintering time of the sintering I is 8 to 16 hours. Thus, the uniformity of W bulk doping and the stability of the crystal structure can be further improved.

[0025] According to a preferred embodiment of the present invention, the sintering temperature of the sintering II is 760-800°C.

[0026] According to a preferred embodiment of the present invention, the sintering time of the sintering II is 1 to 2 hours, thereby further improving the stability of the surface doping of the cerium element and optimizing the effect of refining the particles of the boron element.

[0027] According to a preferred embodiment of the present invention, the nickel source includes at least one of spherical Ni(OH)2, spherical NiO, spherical NiCO3 or spherical NiC2O4.

[0028] According to a preferred embodiment of the present invention, the tungsten source includes at least one of tungsten oxide, tungstic acid, ammonium paratungstate, ammonium tungstate or ammonium metatungstate.

[0029] According to a preferred embodiment of the present invention, the cerium source includes at least one of cerium oxide, cerium nitrate, ammonium ceria, cerium carbonate, cerium acetate or cerium hydroxide.

[0030] According to a preferred embodiment of the present invention, the boron source includes at least one of boric acid and boron oxide (such as boron trioxide).

[0031] According to a preferred embodiment of the present invention, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate or lithium acetate.

[0032] According to a preferred embodiment of the present invention, in step S1, the rotation speed of the ball mill is 300-600 rpm.

[0033] According to a preferred embodiment of the present invention, in step S1, the ball milling time is 4 to 8 hours.

[0034] The third aspect of the present invention provides a positive electrode plate, comprising a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector; the positive electrode active material layer comprises the positive electrode material described in the first aspect of the present invention.

[0035] According to a preferred embodiment of the present invention, the positive electrode active material layer may further include a conductive agent and a binder. The present invention does not specifically limit the types of the conductive agent and the binder in the positive electrode active material layer, and they can be selected according to actual needs.

[0036] As an example, the conductive agent can be one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; the binder can be one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), ethylene-vinyl acetate copolymer (EVA), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorine-containing acrylic resin and polyvinyl alcohol (PVA).

[0037] The positive electrode current collector may be a metal foil or porous metal plate with good electrical conductivity and mechanical properties, and its material may be one or more of aluminum, copper, nickel, titanium, silver and their respective alloys. The positive electrode current collector is, for example, aluminum foil.

[0038] The positive electrode sheet can be prepared according to conventional methods in the art. For example, the positive electrode active material, the conductive agent and the binder are dispersed in a solvent, and the solvent can be N-methylpyrrolidone (NMP) and deionized water to form a uniform positive electrode slurry, and the positive electrode slurry is coated on the positive electrode current collector, and after drying, rolling and other processes, the positive electrode sheet is obtained.

[0039] The fourth aspect of the present invention provides a secondary battery, comprising the positive electrode sheet according to the third aspect of the present invention. Due to the use of the positive electrode material according to the first aspect of the embodiment of the present invention, the secondary battery can have excellent cycle life and rate performance.

[0040] According to a preferred embodiment of the present invention, the secondary battery further comprises a negative electrode sheet, a separator and an electrolyte.

[0041] According to a preferred embodiment of the present invention, the negative electrode plate may be a metallic lithium sheet. The negative electrode plate may also include a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector. For example, the negative electrode current collector includes two opposite surfaces in its own thickness direction, and the negative electrode active material layer is stacked on any one or both of the two surfaces of the negative electrode current collector.

[0042] The negative electrode active material layer includes a negative electrode active material. The present invention does not specifically limit the type of the negative electrode active material, and it can be selected according to actual needs. As an example, the negative electrode active material may be natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO m (0 < m < 2, such as m = 1), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel-structured lithium titanate Li4Ti5O 12 , Li-Al alloy, and metallic lithium, or one or more of them.

[0043] According to a preferred embodiment of the present invention, the negative electrode active material layer may further include a conductive agent and a binder. The present invention does not specifically limit the types of the conductive agent and the binder in the negative electrode active material layer, and they can be selected according to actual needs. As an example, the conductive agent is one or more of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; the binder is one or more of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin, and carboxymethyl cellulose (CMC).

[0044] According to a preferred embodiment of the present invention, the negative electrode active material layer may optionally include a thickening agent, such as carboxymethyl cellulose (CMC).

[0045] According to a preferred embodiment of the present invention, the negative electrode current collector may be made of a metal foil or a porous metal plate with good electrical conductivity and mechanical properties, and its material may be one or more of copper, nickel, titanium, iron, and their respective alloys. The negative electrode current collector is, for example, a copper foil.

[0046] According to a preferred embodiment of the present invention, the negative electrode plate can be prepared by a conventional method in the art. For example, the negative electrode active material, the conductive agent, the binder, and the thickening agent are dispersed in a solvent, and the solvent can be N-methylpyrrolidone (NMP) or deionized water to form a uniform negative electrode slurry. The negative electrode slurry is coated on the negative electrode current collector, and after processes such as drying and rolling, the negative electrode plate is obtained.

[0047] According to a preferred embodiment of the present invention, the electrolyte of the secondary battery of the embodiment of the present invention can be a solid electrolyte, such as a polymer electrolyte, an inorganic solid electrolyte, etc., but is not limited thereto. The electrolyte can also be an electrolyte. As the above-mentioned electrolyte, it includes a solvent and a lithium salt dissolved in the solvent.

[0048] Among them, the solvent can be a non-aqueous organic solvent, such as ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB) and ethyl butyrate (EB) One or more, preferably two or more.

[0049] According to a preferred embodiment of the present invention, the lithium salt may be one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalate borate), LiBOB (lithium bis(oxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorooxalate phosphate) and LiTFOP (lithium tetrafluorooxalate phosphate), for example, one or more of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiBOB (lithium bis(oxalate borate), LiDFOB (lithium difluorooxalate borate), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide) and LiFSI (lithium bis(fluorosulfonyl)imide).

[0050] According to a preferred embodiment of the present invention, the electrolyte may further contain other additives, such as vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), succinonitrile (SN), adiponitrile (ADN), glutaronitrile (GLN), hexanetrinitrile (HTN), 1,3-propane sultone (1,3-PS), vinyl sulfate (DTD), methylene disulfonate (MMDS), 1-propylene -1,3-sultone (PST), 4-methylethylene sulfate (PCS), 4-ethylethylene sulfate (PES), 4-propylethylene sulfate (PEGLST), propylene sulfate (TS), 1,4-butane sultone (1,4-BS), ethylene sulfite (DTO), dimethyl sulfite (DMS), diethyl sulfite (DES), sulfonate cyclic quaternary ammonium salt, tris(trimethylsilyl) phosphate (TMSP) and tris(trimethylsilyl) borate (TMSB) One or more, but not limited thereto.

[0051] According to a preferred embodiment of the present invention, the secondary battery of the embodiment of the present invention has no special restrictions on the isolation membrane, and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected, such as single-layer or multi-layer films of one or more of glass fiber, non-woven fabric, polyethylene (PE), polypropylene (PP) and polyvinylidene fluoride (PVDF).

[0052] According to a preferred embodiment of the present invention, the secondary battery is prepared by a method known in the art, for example, positive electrode sheets and negative electrode sheets are alternately stacked, and a separator is provided between the positive electrode sheets and the negative electrode sheets to play an isolating role, to obtain a battery cell, or the battery cell can be obtained by winding. The battery cell is placed in a housing, an electrolyte is injected, and the housing is sealed to obtain a secondary battery.

[0053] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0055] Figure 1 is a flow chart of the preparation of the positive electrode material of Example 1 of the present invention;

[0056] Figure 2 is the XRD diagram of the positive electrode material of Example 1 of the present invention;

[0057] Figure 3 is a SEM image of the positive electrode material of Example 1 of the present invention;

[0058] Figure 4 is a graph of the first discharge specific capacity of a secondary battery prepared from the positive electrode material of Example 1 of the present invention;

[0059] Figure 5 is a graph of the number of cycles of a secondary battery prepared using the positive electrode material of Example 1 of the present invention;

[0060] Figure 6 This is a rate performance diagram of a secondary battery prepared using the positive electrode material of Example 1 of the present invention. DETAILED DESCRIPTION

[0061] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0062] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0063] Some of the raw materials used in the examples and comparative examples of the present invention are as follows:

[0064] Nickel source: spherical nickel hydroxide; commercially available;

[0065] Tungsten source: tungsten oxide; commercially available;

[0066] Cerium source: cerium oxide; commercially available;

[0067] Boron source: boric acid; commercially available;

[0068] Lithium source: lithium hydroxide; commercially available.

[0069] Example 1

[0070] This example provides a positive electrode material A, whose chemical formula is LiNi 0.97 W 0.01 Ce 0.01 B 0.01 O2; the preparation process diagram is as follows Figure 1 As shown, the preparation method is as follows:

[0071] S1. Weigh tungsten oxide, cerium oxide, boric acid, nickel hydroxide and lithium hydroxide in a molar ratio of 0.01:0.01:0.01:0.97:1.05, mix and put into a high-energy ball mill, and ball mill at a speed of 400 rpm for 6 hours to obtain a precursor;

[0072] S2, placing the precursor in a high temperature furnace and sintering at 680°C for 8 hours to obtain an intermediate;

[0073] S3. Raise the sintering temperature of the intermediate to 800°C and maintain for 2 hours; after sintering, naturally cool to room temperature; and then obtain positive electrode material A through screening and grinding.

[0074] The prepared positive electrode material A was subjected to X-ray diffraction (XRD) test, and the results are as follows Figure 2 As shown, it indicates that the positive electrode material A forms a stable α-NaFeO2 type layered structure with CeO2 as the mixed phase.

[0075] The positive electrode material A was subjected to SEM test, and the results are as follows Figure 3 As shown, it is shown that the particles of the positive electrode material A of the present invention are evenly distributed and small in size.

[0076] Example 2

[0077] This example provides a positive electrode material B, whose chemical formula is LiNi 0.98 W 0.005 Ce 0.01 B 0.005 O2; the preparation method is as follows:

[0078] S1. Weigh tungsten oxide, cerium oxide, boric acid, nickel hydroxide and lithium hydroxide in a molar ratio of 0.005:0.01:0.005:0.98:1.05, mix and put into a high-energy ball mill, and ball mill at a speed of 400 rpm for 6 hours to obtain a precursor;

[0079] S2, placing the precursor in a high temperature furnace and sintering at 720°C for 8 hours to obtain an intermediate;

[0080] S3. Raise the sintering temperature of the intermediate to 760°C and maintain for 2 hours. After sintering, naturally cool to room temperature. Then, screen and grind to obtain positive electrode material B.

[0081] Example 3

[0082] This example provides a positive electrode material C, whose chemical formula is LiNi 0.98 W 0.005 Ce 0.005 B 0.01 O2; the preparation method is as follows:

[0083] S1. Weigh tungsten oxide, cerium oxide, boric acid, nickel hydroxide and lithium hydroxide in a molar ratio of 0.005:0.005:0.01:0.98:1.05, mix and put into a high-energy ball mill, and ball mill at a speed of 400 rpm for 6 hours to obtain a precursor;

[0084] S2, placing the precursor in a high temperature furnace and sintering at 720°C for 16 hours to obtain an intermediate;

[0085] S3. Raise the sintering temperature of the intermediate to 780°C and maintain for 2 hours. After sintering, naturally cool to room temperature. Then, screen and grind to obtain positive electrode material C.

[0086] Comparative Example 1

[0087] This example provides a positive electrode material D, whose chemical formula is LiNi 0.98 Ce 0.01 B 0.01 O2; the preparation method is as follows:

[0088] S1. Weigh cerium oxide, boric acid, nickel hydroxide and lithium hydroxide in a molar ratio of 0.01:0.01:0.98:1.05, mix and put into a high-energy ball mill, and ball mill at a speed of 400 rpm for 6 hours to obtain a precursor;

[0089] S2, placing the precursor in a high temperature furnace and sintering at 680°C for 8 hours to obtain an intermediate;

[0090] S3. Raise the sintering temperature of the intermediate to 800°C and maintain for 2 hours. After sintering, naturally cool to room temperature. Then, screen and grind to obtain positive electrode material D.

[0091] Comparative Example 2

[0092] This example provides a positive electrode material E, whose chemical formula is LiNi 0.98 W 0.01 B 0.01 O2; the preparation method is as follows:

[0093] S1. Weigh tungsten oxide, boric acid, nickel hydroxide and lithium hydroxide in a molar ratio of 0.01:0.01:0.98:1.05, mix and put into a high-energy ball mill, and ball mill at a speed of 400 rpm for 6 hours to obtain a precursor;

[0094] S2, placing the precursor in a high temperature furnace and sintering at 680°C for 8 hours to obtain an intermediate;

[0095] S3. Raise the sintering temperature of the intermediate to 800°C and maintain for 2 hours; after sintering, naturally cool to room temperature; and then obtain positive electrode material E through screening and grinding.

[0096] Comparative Example 3

[0097] This example provides a positive electrode material F, whose chemical formula is LiNi 0.98 Ce 0.01 W 0.01 O2; the preparation method is as follows:

[0098] S1. Weigh cerium oxide, tungsten oxide, nickel hydroxide and lithium hydroxide in a molar ratio of 0.01:0.01:0.98:1.05, mix and put into a high-energy ball mill, and ball mill at a speed of 400 rpm for 6 hours to obtain a precursor;

[0099] S2, placing the precursor in a high temperature furnace and sintering at 680°C for 8 hours to obtain an intermediate;

[0100] S3. Raise the sintering temperature of the intermediate to 800°C and maintain for 2 hours; after sintering, naturally cool to room temperature; and then obtain positive electrode material F through screening and grinding.

[0101] Performance Testing

[0102] The positive electrode materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 are prepared into lithium ion secondary batteries; the specific method is as follows:

[0103] Positive electrode sheet: The positive electrode materials of Examples 1 to 3 and Comparative Examples 1 to 3 were mixed with acetylene black as a conductive agent and polytetrafluoroethylene as a binder at a mass ratio of 8:1:1, and ground evenly, and coated on aluminum foil, and dried at 80°C for 12 hours.

[0104] Negative electrode: metal lithium sheet;

[0105] Electrolyte: 1 mol / L lithium hexafluorophosphate (LiPF6) mixed solution of ethylene carbonate (EC) and diethyl carbonate (DEC) (3:7, v:v) plus 1% volume fraction of vinylene carbonate (VC).

[0106] Separator film: Polypropylene film (Celgard 2400).

[0107] The positive electrode sheet, negative electrode sheet, electrolyte and separator were assembled into a CR2032 type button lithium ion battery, and the following electrical performance tests were performed in the voltage window of 2.7-4.3V. The results are shown in Table 1.

[0108] 0.2C first discharge specific capacity test method: At 30°C, charge the button lithium-ion battery at 0.2C constant current to 4.3V, then charge at 4.3V constant voltage to a current less than 0.02C, then discharge the button battery at constant current to 3V, and calculate the first discharge specific capacity.

[0109] Cycle performance test method: At 30°C, charge the button lithium-ion battery at 1C constant current to 4.3V, then charge at 4.3V constant voltage until the current is less than 0.01C; then discharge at 1C constant current to 3V for a complete cycle. Repeat the above charge and discharge process 200 times, record the discharge capacity of each cycle, and analyze the change of discharge capacity with the number of cycles to evaluate the battery's 1C cycle performance. The capacity retention rate (%) of the lithium-ion battery after 200 cycles at 30°C = (discharge capacity of the 200th cycle / first discharge capacity) × 100%.

[0110] Rate performance test method: At 30°C, the button lithium-ion battery is charged to 4.3V at 0.2C, 0.5C, 1C, 3C, 5C and 10C in sequence, and then charged at 4.3V constant voltage until the current is less than 0.01C; then discharged at the same rate constant current to 3V as one cycle. Each rate is tested for 5 cycles, the discharge capacity is recorded and the average value is calculated. The discharge capacity at a certain rate is the average of the 5 discharge capacities at that rate.

[0111] Table 1

[0112]

[0113] The secondary battery of Example 1 was tested for the 0.2C initial discharge specific capacity; the results are shown in Figure 4 ; 0.2C first discharge specific capacity up to 205.4mAh g -1 The results of the cycle performance test are as follows Figure 5 , the capacity retention rate after 200 cycles at 1C is 85.2%; the rate performance test results are as follows Figure 6 The discharge capacity at 10C rate is 178.2 mAh g -1 .

[0114] From the data in Table 1, it can be seen that the present invention greatly improves the cycle capacity retention rate and rate performance of the high-nickel cobalt-free positive electrode material by introducing tungsten, boron and cerium to synergistically dope the high-nickel cobalt-free positive electrode material.

[0115] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A positive electrode material, characterized in that: The chemical formula of the positive electrode material is LiNi (1-x-y-z) W x Ce y B z O2; Among them, 0<x≤0.01; 0<y≤0.01; 0<z≤0.

01.

2. The positive electrode material according to claim 1, characterized in that An α-NaFeO2 type layered structure is formed in the positive electrode material.

3. The positive electrode material according to claim 1 or 2, characterized in that The average particle size of the secondary particles of the positive electrode material is 8 μm to 16 μm.

4. A method for preparing the positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: S1, mixing a nickel source, a tungsten source, a cerium source, a boron source and a lithium source and ball milling them to obtain a precursor; S2, sintering the precursor to obtain an intermediate; S3. Sintering the intermediate II and grinding it to obtain a positive electrode material.

5. The preparation method according to claim 4, characterized in that: The sintering temperature of the sintering I is 680-720°C.

6. The preparation method according to claim 4, characterized in that: The sintering time of the sintering I is 8 to 16 hours.

7. The preparation method according to claim 4, characterized in that: The sintering temperature of the sintering II is 760-800°C.

8. The preparation method according to claim 4, characterized in that: The sintering time of the sintering II is 1 to 2 hours.

9. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector and a positive electrode active material layer arranged on the positive electrode current collector; the positive electrode active material layer comprises the positive electrode material according to any one of claims 1 to 3.

10. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Modified positive electrode material and modification method thereof

    CN114420935A

  • Cobalt-free and manganese-free positive electrode material as well as preparation method and application thereof

    CN114512663A

  • Lithium-rich manganese-based positive electrode material and preparation method and application thereof

    CN117164019A